Implementasi Metode Musyabahah Dalam Pembelajaran Mufradat Bahasa Arab Pada Mahasiswa PBA Universitas Al-Falah Assunniyyah (UAS) Kencong, Jember - Zaeni, Akhmad; Taubah, Miftachul (An-Nuqthah, 2023)
The selection of the musyabahah method used specifically in learning Arabic can be used as an alternative learning method. The primary data sources are the results of interviews and observations, the secondary data sources are the latest book "Al-Arabiyah Baina Yadaik" Volume 2. The data collection techniques are observation, interviews and documentation as well as a combination of the three, using the Miles and Huberman model data analysis techniques. The results of its implementation are: (1) The lecturer reveals basic Arabic words that are musyabahah, prepares Arabic mufradat to train students' cognitive thinking skills in finding Indonesian equivalents, (2) Students study and compile mufradat musyabahah discussing material in their books, then mention the findings each mufradat musyabahah, (3) The lecturer explains the assimilated vocabulary sounds with different letters but more or less the same.